1983
DOI: 10.1002/1097-0142(19830715)52:2<301::aid-cncr2820520218>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical staining for CEA in small cell carcinoma of lung predicts clinical usefulness of the plasma assay

Abstract: Recent studies have shown plasma CEA levels are useful in both staging and monitoring response to treatment in patients with small cell cancer of the lung (SCCL). CEA elevations do not occur in all patients however, and have been of less value in patients with limited disease. Immunoperoxidase staining for CEA performed on tumor tissue from 48 patients (17 extensive, 31 limited disease) with SCCL revealed: (1) A strong correlation between positive CEA tissue staining and plasma CEA elevation. Plasma CEA elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Most SCLC cell lines express significant levels of a3/3~ integrin (Hemler et al, 1990;Feldman et al, 1991), NCAM (Kibbelaar et al, 1989;Patel et al, 1989;Aletsee-Ufrecht et al, 1990;Rygaard et al, 1992), and the NCAM-associated epitope CD57 , similar to the cells lines we studied. More variable expression of ICAM-1 (Boyd et al, 1989), CEA (Goslin et al, 1983;Bepler et al, 1989), and N-cadherin (Rygaard et al, 1992) has been reported for different SCLC cell lines. A previous study demonstrated the expression of E-cadherin at cell junctions in SCLC biopsies taken from two independent cases (Shimoyama et al, 1989).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most SCLC cell lines express significant levels of a3/3~ integrin (Hemler et al, 1990;Feldman et al, 1991), NCAM (Kibbelaar et al, 1989;Patel et al, 1989;Aletsee-Ufrecht et al, 1990;Rygaard et al, 1992), and the NCAM-associated epitope CD57 , similar to the cells lines we studied. More variable expression of ICAM-1 (Boyd et al, 1989), CEA (Goslin et al, 1983;Bepler et al, 1989), and N-cadherin (Rygaard et al, 1992) has been reported for different SCLC cell lines. A previous study demonstrated the expression of E-cadherin at cell junctions in SCLC biopsies taken from two independent cases (Shimoyama et al, 1989).…”
Section: Discussionmentioning
confidence: 93%
“…We are investigating factors controlling the adhesion of small cell lung carcinoma (SCLC) cells. SCLC cells express NCAM (Kibbelaar et al, 1989;Patel et al, 1989;Aletsee-Ufrecht et al, 1990;Rygaard et al, 1992), ICAM-1 (Boyd et al, 1989), carcinoembryonic antigen (CEA) (Goslin et al, 1983;Bepler et al, 1989), and members of the integrin (Hemler et al, 1990;Feldman et al, 1991) and cadherin (Shimoyama et al, 1989;Rygaard et al, 1992) gene families. SCLC cells also express receptors for neurotransmitters (Sorenson et al, 1983;Cunningham et al, 1985;Maneckjee and Minna, 1990;Williams and Lennon, 1990) and autocrine growth factors (for review see Weynants et al, 1990), and it is possible that activation of these receptors may modulate the expression or activity of SCLC adhesion molecules.…”
mentioning
confidence: 99%
“…In lung cancer, CEA can also be a useful biomarker. CEA is elevated in approximately two-thirds of nonsmall cell lung cancer patients and one-third of those with small cell lung cancer (134)(135)(136). Both the frequency and levels of CEA elevation are considerably lower in patients with benign lung diseases.…”
Section: Cea As a Diagnostic Testmentioning
confidence: 99%
“…Επίσης, στα μικροκυτταρικά καρκινώματα του πνεύμονα φαίνεται ότι τα επίπεδα του CEA στον ορό σχετίζονται με το στάδιο της νόσου, όπως αναφέρουν οι Vincent et al (210) , οι Gronowitz et al (223) , οι Krischke et al (253) , οι Waalkes et al (280) , οι Goslin et al (281) και οι Soulier et al (282) . Οι Hida et al (271) αναφέρουν ότι μόνον 15,7% των ασθενών που πάσχουν από βρογχογενή καρκινώματα έχουν αυξημένα επίπεδα SCC-Ag στον ορό τους.…”
Section: All Grades Grade a Grade β Grade Cunclassified